The Relationship between Annual Airborne Pollen Levels and Occurrence of All Cancers, and Lung, Stomach, Colorectal, Pancreatic and Breast Cancers: A Retrospective Study from the National Registry Database of Cancer Incidence in Japan, 1975–2015 - Akira Awaya (International Journal of Environmental Research and Public Health, 2020)
Suppression of risk factors including smoking, overdrinking and infections by human papilloma and hepatitis B and C viruses has been recommended for cancer prevention; however, identification of other environmental risk factors has not been enough. Besides the 2003 report that Kawasaki disease may be triggered by pollen exposure, 40 Japanese specific intractable diseases have recently been reported as “pollen diseases,” also potentially triggered by pollen exposure．Various human organs are affected by pollen exposure, leading to systemic vasculitis; autoimmune connective tissue diseases, inflammatory bowel diseases and intractable neuromuscular and bone diseases, suggesting the common effects of pollen exposure on fundamental functions of vital metabolism. In this context, cancer and malignant tumors may be another group of intractable diseases triggered by epigenetic pollen exposure. Thus, this study compared the number of newly registered patients with 24 types of cancer and airborne pollen levels measured from 1975 to 2015. We searched for statistical correlations with Bonferroni correction between the annual number of newly registered patients for all cancers or for each of lung, stomach, colorectal, pancreatic and breast cancers in the patient-registry year “x”, and annual airborne pollen levels measured in the same year as “x”, or 1–7 years prior to the year “x”. The number of newly registered patients for lung, and pancreatic cancers in the patient-registry year “x” was highly correlated with airborne pollen levels measured 2 years prior to “x”. That for breast cancer was correlated with pollen levels measured 2 and 5 years prior to “x”. To our knowledge, this is the first rapid communication of the association between pollen levels and cancer incidence.